Review of the book „Energy systems in transportation“ by Leonid Ivanovich Gretchihin and N. G. Kuch (Леонид Иванович Гречихин и Н. Г. Куць) - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The book describes the efficiency and operation of internal combustion engines and analyzes the main tendencies in improving their operation. The efficiency of rotary engines such as those of Wankel,  Isayev, Sedunov and Ivanov has been given in detail as well as the operation of engines where the rotor has the function of turbine blades. The efficiency of the operation of turbo compressor and turbo reactive engines has been analyzed as well. The effects of stationary and nonstationary heat conduction on the efficiency of heat engine operation have been also discussed. The main part of the book deals with the analysis of the efficiency of the operation of hybrid energy systems with the application of heat pumps.
Keywords: energy complexes; transportation; Engines; energy use; Efficiency